Wpływ dysproporcji rozwojowych na specyfikę kształtowania dochodów jednostek samorządu terytorialnego na Lubelszczyźnie - Śmiechowicz, Joanna (Development Disparities and Character of Self-Government Revenues in Lubelskie, 2007)
This article comprises the characteristics of Lubelskie voivodeship as the poorest region of Poland and the EU. The publication also presents the consequences for self-government revenues in the region. Development disparities impend economic, social and territorial cohesion of the country and simultaneously are being inconsistent with the European Community principals. The Polish system of self-government revenues likewise compulsory regulations of the European Union tend to equalize financial base of units responsible for local affairs and development including territorial self-government.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 562-573